1993
DOI: 10.1002/tea.3660300805
|View full text |Cite
|
Sign up to set email alerts
|

A content analysis of research published in the Journal of Research in Science Teaching from 1985 through 1989

Abstract: To determine if actual practice was consistent with commonly recommended research methods and procedures, this study examined 130 studies reported over a 5‐year period in three volumes of the Journal of Research in Science Teaching (JRST). The results were consistent with similar previous analyses (Shaver & Norton, 1980a, 1980b; Wallen & Fraenkel, 1988a) and indicate that appropriate generalizations beyond the confines of the reported studies may be impossible for most (64%) of the JRST studies surveyed. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Inherent in all classroom-based studies is a certain amount of variability in teaching practices between treatment groups. Differences in subject characteristics is an internal validity concern to all studies, and nearly half of studies do not address it properly (Horton et al, 1993). However, given that the Teacher of Record was the same for each class in this instance, the threat was controlled for as best as possible.…”
Section: Threatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inherent in all classroom-based studies is a certain amount of variability in teaching practices between treatment groups. Differences in subject characteristics is an internal validity concern to all studies, and nearly half of studies do not address it properly (Horton et al, 1993). However, given that the Teacher of Record was the same for each class in this instance, the threat was controlled for as best as possible.…”
Section: Threatsmentioning
confidence: 99%
“…The Hawthorne effect is a concern for all field experiments, present in 48% (Horton et al, 1993); it can be defined as ''the problem in field experiments that subjects' knowledge that they are in an experiment modifies their behavior from what it would have been without the knowledge'' (Adair, 1984, p. 334). When applied to teaching situations like those in this study, the Hawthorne effect can have positive implications.…”
Section: Threatsmentioning
confidence: 99%
“…In addition, the publication rate of replications in marketing journals had declined since the 1970s. According to Horton and colleagues (1993), of the 130 studies published in a five-year period in the Journal of Research in Science Teaching , only 3 percent were intended by the author to be a direct replication of an earlier study. Finally, Kelly’s examination of the three top journals in behavioral ecology (2006) found no true replications, with most studies categorized as quasi-replications.…”
Section: Performance and Publication Of Replication Researchmentioning
confidence: 99%
“…), and particular languages (e.g., French [Martinand & Giordan, 1989]), but no reviews of this kind are based specifically on higher degrees awarded in science education. While summaries and analytical reviews highlighting trends in the content of research studies in science education have, for example, been conducted on particular research domains (e.g., students' conceptions [Duit, 1993]), on research reported in particular journals (e.g., [White;cited in Rennie, Fraser, & Treagust, 1999]), and on the methods and procedures employed in research studies (e.g., Horton et al, 1993), these analyses have not focused on research conducted for higher degrees. Summaries of research published in particular years (e.g., Lederman, Gess-Newsome, & Zeidler, 1993) have referenced graduate degrees (and then only doctorates) but not summarized or reviewed them.…”
Section: Introductionmentioning
confidence: 99%